Impact of trace mineral supplementation and translucency score on eggshell quality, hatchability, fertility, and chick quality - Cassidy A. Morris; Duarte Neves; Michael Carroll; Jonathan Moon; Leticia Orellana; Raquel Burin; Colwayne Morris; Austin Jasek; Kenneth S. Macklin (Poultry Science)
ABSTRACT: The broiler breeder industry is facing a problem with fertility, hatchability, and the number of broiler breeder eggs produced per hen. The supplementation of trace minerals such as zinc, manganese, and copper in broiler breeder diets has been previously linked to an increase in eggshell quality, which may lead to increased fertility, hatchability, and chick quality. The objective of this study was to explore the effect of amino-acid complexed mineral supplementation on eggshell quality, fertility, hatchability, chick quality, and shell translucency. Translucency score was tested to determine if it would impact other eggshell quality parameters. To evaluate this, zinc, manganese, and copper were added into the water of commercial broiler breeder houses at the levels of 40, 40, and 7 ppm, respectively, for 10 wk. This was conducted on 4 farms with one house receiving mineral supplementation (T) and another house on the same farm receiving no supplementation (C). A total of 5,120 eggs were collected after 10 wk and analyzed for translucency score (TS1-3; low-high), eggshell lightness (L* score), thickness, and breaking strength. Up to 60 infertile eggs per farm underwent microbial analysis to determine bacteria and E. coli prevalence on d 18 of incubation. All data was analyzed using PROC-GLM or chi-square with P ≤ 0.05; means were separated by Tukey's when appropriate. The results showed that mineral supplementation increased the L* score from 74.9 (C) to 75.1 (T) (P = 0.0245), shell thickness from 0.451 mm to 0.455 mm (P = 0.0402), TS1 eggs by 1.05%, TS2 eggs by 5.86%, and decreased TS3 eggs by 6.91% (P < 0.0001). Shell thickness differed (P < 0.0001) between all levels of translucency. Significance was also found for L* score (P < 0.0001) between TS3 eggs (74.2) when compared to TS1 (74.8) and TS2 (75.2) eggs. Improvements in fertility (83.0% C vs. 86.1% T) and hatchability (74.3% C vs. 76.8% T) were not statistically significant. It can be concluded that amino-acid complexed mineral supplementation improves eggshell quality, particularly shell translucency score, leading to potential improvements in commercial breeder operations.